The anaesthesia science viva book : clinical science as applied to anaesthesia, intensive therapy and chronic pain : a guide to the oral questions - Bricker, Simon (Cambridge : Cambridge University Press, 2017)
This third edition of the highly successful The Anaesthesia Science Viva Book contains detailed, accessible summaries of the core questions in anatomy, physiology, pharmacology and clinical measurement that may be asked in the oral section of the Final FRCA exam. In addition to comprehensive updating of all the topics, this edition includes new subject material in each of the four basic sciences, with almost 200 detailed summaries of the most relevant topics in the examination. This volume once again gives candidates an insight into the way the viva works; offering general guidance on exam technique, and providing readily accessible information relating to a wide range of potential questions. Written by a former senior examiner for the diploma of the Fellowship of the Royal College of Anaesthetists and listed as recommended reading by AnaesthesiaUK, the prime educational resource for trainee anaesthetists, it remains an essential purchase for every Final FRCA candidate.
Advice on answering clinical science viva questions -- Anatomy and its applications -- Physiology -- Pharmacology -- Physics and clinical measurement.
Title from publisher's bibliographic system (viewed on 30 Aug 2017).
Keywords: Anesthesia -- Examinations -- Study guides